Recommendations from the Italian Society of Pediatric Orthopaedics and Traumatology for the management of pediatric orthopaedic patients during the COVID19 pandemic and post-pandemic period in Italy - Giovanni Trisolino; Carlo Enrico Origo; Nando De Sanctis; Daniela Dibello; Pasquale Farsetti; Cosimo Gigante; Pasquale Guida; Lorenza Marengo; Elena Panuccio; Renato Maria Toniolo; Fabio Verdoni; Antonio Memeo (BMC, 2020)
Abstract The rapid spread of the COVID-19 outbreak in Italy has dramatically impacted the National Healthcare System, causing the sudden congestion of hospitals, especially in Northern Italy, thus imposing drastic restriction of almost all routine medical care. This exceptional adaptation of the Italian National Healthcare System has also been felt by non-frontline settings such as Pediatric Orthopaedic Units, where the limitation or temporary suspension of most routine care activities met with a need to maintain continuity of care and avoid secondary issues due to the delay or suspension of the routine clinical practice. The Italian Society of Pediatric Orthopaedics and Traumatology formulated general and specific recommendations to face the COVID-19 outbreak, aiming to provide essential care for children needing orthopaedic treatments during the pandemic and early post-peak period, ensure safety of children, caregivers and healthcare providers and limit the spread of contagion.